2010
DOI: 10.1111/j.1570-7458.2010.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of partial sterility in mating performance and reproduction of the West Indian sweetpotato weevil, Euscepes postfasciatus

Abstract: The sterile insect technique (SIT) is based on population and behavioral ecology and is widely used to suppress or eradicate target pest insect populations. The effectiveness of SIT depends on the ability of the released sterile males to mate with and inseminate wild females. The use of gamma-radiation to induce sterility is, however, associated with negative impacts not only on reproductive cells but also on somatic cells. Consequently, irradiation for sterilization diminishes mating performance over time. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Therefore, prolongation of the effective mating propensity of weevils would lead to cost savings, and thus be useful for population management programmes using SIT. Although partial sterilization by low‐dose irradiation yields this advantage for E. postfasciatus (Kumano et al , 2010a, b), the application of partially sterilized weevils is limited in the early stage of eradication programme using the SIT method as a result of their fertilization ability (Knipling, 1955, 1979; Suzuki & Miyai, 2000; Toledo et al , 2004; Rull et al , 2007). For example, the fertilization ability of weevils irradiated with a dose of 125 Gy was reduced by 4.6% in males and 0.6% in females, relative to the potential fertilization ability (Kumano et al , 2010a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, prolongation of the effective mating propensity of weevils would lead to cost savings, and thus be useful for population management programmes using SIT. Although partial sterilization by low‐dose irradiation yields this advantage for E. postfasciatus (Kumano et al , 2010a, b), the application of partially sterilized weevils is limited in the early stage of eradication programme using the SIT method as a result of their fertilization ability (Knipling, 1955, 1979; Suzuki & Miyai, 2000; Toledo et al , 2004; Rull et al , 2007). For example, the fertilization ability of weevils irradiated with a dose of 125 Gy was reduced by 4.6% in males and 0.6% in females, relative to the potential fertilization ability (Kumano et al , 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…The mating propensity of irradiated males receiving two or three doses totalling 150 Gy did not significantly differ from that of non‐irradiated control males for the first 12 days after irradiation. Because the duration of effective mating propensity of fractionated irradiated male E. postfasciatus is equal to that of partially‐sterilized E. postfasciatus males irradiated with doses in the range 75–125 Gy (Kumano et al , 2010a), partially sterilized weevils have no particular advantage in an eradication programme that depends upon fertilization ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2008a) demonstrated that acute irradiation dramatically decreased male mating propensity with time, prolonging the effective mating propensity of sterilized weevils is very useful for population management programs using SIT. Although partial sterilization in the early stage of an eradication program by low‐dose irradiation yields this advantage in C. formicarius and E. postfasciatus , the short effective copulation period of fully sterilized weevils delays the progress of the eradication program in the last stage in these two weevils (Kumano et al., 2008a,b, 2010a,b). Fractionated‐dose irradiation with full sterilization could mitigate this problem because the mating propensity of irradiated males receiving three doses, totaling 201 Gy, did not significantly differ from that of non‐irradiated control males for 16 days after irradiation in experiment 2.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these problems were solved if the insects were sterilized after being treated with the anti-leukemia drug busulfan or under low doses of fractioned radiation, and egg hatch was avoided by using chitin synthesis inhibitor (Haynes & Smith, 1992;Klassen & Earle, 1970;McKibben et al, 2001). Other detrimental impacts of radiation, such as the collapse of the epithelial tissue of the midgut, were also reported for the West Indian sweetpotato weevil, Euscepes postfasciatus Fairmare, target of an Area-Wide-IPM program in Japan (Kumano et al, 2010 (James, 1947) and Parish (1942) reported 6,148 myiasis cases during the screwworm seasons from 1936 to 1940 on Texas. The economic losses at the southeast and southwest regions of USA were estimated in US$ 20 million/year and US$ 50-100 million/year respectively (Baumhover, 1966).…”
Section: Ordermentioning
confidence: 99%